2009
DOI: 10.5194/acp-9-2275-2009
|View full text |Cite
|
Sign up to set email alerts
|

Hydration of the lower stratosphere by ice crystal geysers over land convective systems

Abstract: Abstract. The possible impact of deep convective overshooting over land has been explored by six simultaneous soundings of water vapour, particles and ozone in the lower stratosphere next to Mesoscale Convective Systems (MCSs) during the monsoon season over West Africa in Niamey, Niger in August 2006. The water vapour measurements were carried out using a fast response FLASH-B Lyman-alpha hygrometer. The high vertical resolution observations of the instrument show the presence of accumulation of enhanced water… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
101
1
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 107 publications
(112 citation statements)
references
References 47 publications
9
101
1
1
Order By: Relevance
“…Considering the different nature of the two platforms (i.e., fast flying aircraft vs. slowly ascending balloon) and the difference in location (Ouagadougou vs. Niamey with ≈430 km separation) the agreement between the two different instruments is good for the theta levels between 360 and 460 K. In the balloon data the rate of increase in mixing ratios with altitude is stronger than for COPAS at theta levels above 450 K. Furthermore, the balloon data show that the enhanced particle number densities are reaching up to ≈550 K, forming a broad layer. The presence of this layer is confirmed also by Khaykin et al (2009), where all balloon flights from Niamey are presented. Because the enhancement does not occur in the mid-latitude and subtropical profiles over Verona, Italy, and Marrakesh, Morocco, the stratospheric enhancement seems to be confined to the tropical belt.…”
Section: Volcanic Influence On the Ut/ls Aerosol Over West Africasupporting
confidence: 54%
See 1 more Smart Citation
“…Considering the different nature of the two platforms (i.e., fast flying aircraft vs. slowly ascending balloon) and the difference in location (Ouagadougou vs. Niamey with ≈430 km separation) the agreement between the two different instruments is good for the theta levels between 360 and 460 K. In the balloon data the rate of increase in mixing ratios with altitude is stronger than for COPAS at theta levels above 450 K. Furthermore, the balloon data show that the enhanced particle number densities are reaching up to ≈550 K, forming a broad layer. The presence of this layer is confirmed also by Khaykin et al (2009), where all balloon flights from Niamey are presented. Because the enhancement does not occur in the mid-latitude and subtropical profiles over Verona, Italy, and Marrakesh, Morocco, the stratospheric enhancement seems to be confined to the tropical belt.…”
Section: Volcanic Influence On the Ut/ls Aerosol Over West Africasupporting
confidence: 54%
“…Fierli (unpublished) and Khaykin et al (2009), do show evidence for overshooting over West Africa. As a result evaporation of the ice particles lead to hydration within the TTL and lower tropical stratosphere (Corti et al, 2008) during TROCCINOX and SCOUT-O3.This is in reasonable agreement with the analysis of Law et al (2010), although they found an influence from lower stratospheric air in the mid and upper TTL during the SCOUT-AMMA campaign period.…”
Section: Atmospheric Background In 2005 and 2006mentioning
confidence: 99%
“…This suggests that anthropogenic aerosol emissions may play a role in determining the amount of moistening produced by overshoots and possibly therefore the global water flux into the stratosphere if the overall effect of overshoots is globally important. In summary, the HIBISCUS and TROCCINOX water vapour and particles measurements were all suggesting moistening of the lower stratosphere by injection of ice crystals by overshooting towers over a convective land region, as observed over Northern Australia Knollenberg et al, 1993;Corti et al, 2008), and Africa (Khaykin et al, 2009), confirmed by the heavier isotopic composition of the water vapour in the stratosphere, characteristic of ice lofted from the troposphere, as observed by Hanisco et al (2007) in situ on the NASA WB-57 aircraft, or remotely by the MIPAS HDO measurements in the stratosphere (Steinwagner et al, 2010). The process, successfully simulated by Grosvenor et al (2007) and Chaboureau et al (2007), is now consistently reproduced by meso-scale non-hydrostatic models (Jensen et al, 2007;Chemel et al, 2009;Hassim et al, 2010).…”
Section: Hydration Of the Lower Stratosphere Over Land Convective Sysmentioning
confidence: 99%
“…A considerable amount of observational evidence for cross-tropopause mass transport through convective overshooting has been made available by recent field campaigns in South America, Australia and Africa, revealing penetration of tropospheric air and ice crystals up to 19-20 km over land convective systems (Nielsen et al, 2007;Corti et al, 2008;Khaykin et al, 2009;de Reus et al, 2009;. Such convective updrafts of adiabatically cooled air and ice crystals across the tropopause are well captured by mesoscale cloud resolving models (Chaboureau et al, 2007;Jensen et al, 2007;Grosvenor et al, 2007;Chemel et al, 2009;Liu et al, 2010), but, because of their non-hydrostatic nature, they are missed by global meteorological and climate models.…”
Section: S M Khaykin Et Al: Impact Of Land Convection On Temperatumentioning
confidence: 99%